2017
DOI: 10.1002/hed.24689
|View full text |Cite
|
Sign up to set email alerts
|

Utility approach to decision-making in extended T1 and limited T2 glottic carcinoma

Abstract: Patients show no clear preference for the outcomes of laser surgery or radiotherapy from a quality of life (QOL) or voice handicap point of view. These data can now be incorporated into decision-making models. © 2017 Wiley Periodicals, Inc. Head Neck, 2017 © 2016 Wiley Periodicals, Inc. Head Neck 39: 779-785, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…A study by van Loon et al investigated the time trade off in patients with laryngeal cancer and concluded that none of the patients who were treated with TLM was prepared to trade off years to live in perfect health. This shows that the perceived side effects (e.g., dysphonia) by patients are not substantial and that patients are able to cope well with their limitations in daily life [37]. QoL is a multidimensional construct; thus, it is best measured with an instrument that reports on multiple domains of functionality and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…A study by van Loon et al investigated the time trade off in patients with laryngeal cancer and concluded that none of the patients who were treated with TLM was prepared to trade off years to live in perfect health. This shows that the perceived side effects (e.g., dysphonia) by patients are not substantial and that patients are able to cope well with their limitations in daily life [37]. QoL is a multidimensional construct; thus, it is best measured with an instrument that reports on multiple domains of functionality and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…20 On the other hand, the systematic review by Huang et.al reported the advantage of Radiotherapy as an increased maximum phonation time and reduced fundamental frequency.+7 But some of the studies showed no significant difference among the outcomes. 4,21 Looking over the recurrence rate, majority of the patients with Laser surgery had tumor recurrence within 9 months to 1 year 22 , while the patients treated with Radiotherapy showed lower recurrence with high disease-free survival 23 , but these findings are contradictory to current study that showed recurrence within 22 months in Radiotherapy treated patients. A Japanese study supported the findings of current study by reporting recurrence within 18 months among patients treated with Radiotherapy.…”
Section: Discussionmentioning
confidence: 61%
“…The recommended approaches for early stage glottic carcinoma are both laser surgery (LS) as well as radiotherapy (RT). [1][2][3][4] Comparison of both modalities reveals that Laser Surgery is predominant over Radiotherapy in local control of tumor along with preservation of laryngeal anatomy. 3,5,6 Both modalities having some merits as well as demerits like Laser Surgery is expensive, quick, inch-perfect and improvement in hemostasis but require surgical skills and feasibility on the other hand Radiotherapy require longer duration of treatment and the lesion follows the sequel of fibrosis and mucosal edema.…”
Section: Introductionmentioning
confidence: 99%
“…LS has plenty of unique advantages. It can achieve precise cutting, bloodless operation, short operation time, and significantly reduce the recurrence rate 11,1820. Besides, the length of hospital stay will be shortened, and the cost of hospitalization is greatly reduced 21…”
Section: Discussionmentioning
confidence: 99%